Penerapan Alternatif Akad Pembiayaan Haji dan umrah Pasca Peraturan Menteri No 24 Tahun 2016 Pada Bank Panin Dubai Syariah Surabaya - Fitrotu Aini (Universitas Muhammadiyah Surabaya, 2018)
ABSTRACTHajj as a great symbol of worship. Hajj is the fifth pillar of Islam which is mandatory for every Muslim who are able to da it in accordance with the legal requirement of pilgrimage. One of the legal conditions of Hajj is the capability, capable to cover the cost of the hajj and the family left behind. Panin Bank Dubai Sharia Bank was established based on the regulation of Limited Company No. 12 dated January 8, 1972 by Moeslim Dalidd, a notary in Malang. PT. Bank Panin Dubai Syariah Tbk has been legalized by the Financial Services Authority (